Joints and wood shear walls modelling II: Experimental tests and FE models under seismic loading. (15th October 2015) - Boudaud, C.; Humbert, J.; Baroth, J.; Hameury, S.; Daudeville, L.
Highlights: Eleven shake table tests are performed on shear walls. Predictions of the refined FE model of shear wall are compared to all these tests. A simplified FE model of shear wall is proposed and validated for dynamic loading. An efficient discretisation method of a wall into simplified elements is proposed. Abstract: This study presents a finite element (FE) model of timber-framed shear walls under seismic loading, which has been validated in Part I under quasi-static loading. In this paper, experimental shake table tests on shear walls are described and some examples of the obtained results are discussed. Then, the refined FE model predictions under dynamic loading are compared to the 11 shake table tests. The final objective of this study is to create a 3D model of timber-framed structures; thus, a simplified FE model is proposed to reproduce the refined FE model predictions at a reasonable computational cost. The calibration method of the simplified model uses the predictions of the refined FE model under quasi-static loading as input. The simplified model is then used for dynamic calculations and its predictions are confronted to the refined FE model ones, in order to validate its behaviour under dynamic loading. Eventually, an efficient method to build the walls of a timber-framed building by coupling simplified FE models is proposed.